1998
DOI: 10.1104/pp.118.3.835
|View full text |Cite
|
Sign up to set email alerts
|

Source and Magnitude of Ammonium Generation in Maize Roots

Abstract: Short-term studies with 13 NH 4 ϩ have provided estimates of NH 4 ϩ influx, efflux, and cytoplasmic concentration in spruce (Kronzuker et al., 1995a(Kronzuker et al., , 1995b. As the NH 4 ϩ concentration in the external solution increased from 10 to 1500 m, cytosolic NH 4 ϩ levels increased from 2 to 33 mm and efflux increased from 10% to 35% of influx. Similar rates were reported for rice: as external NH 4 ϩ levels increased from 2 to 1000 m, cytosolic NH 4 ϩ levels increased from 3 to 38 mm and efflux rose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Asn acts as a nitrogen storage compound synthesized under high concentrations of ammonium and thus acts in ammonium detoxification (Givan, 1979;Sieciechowicz et al, 1988). Higher levels of ammonium cannot only be due to uptake from the environment but also result from the catabolism of soluble organic nitrogen in maize roots (Feng et al, 1998). This emphasizes a role of Asn synthetase in ammonium assimilation in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Asn acts as a nitrogen storage compound synthesized under high concentrations of ammonium and thus acts in ammonium detoxification (Givan, 1979;Sieciechowicz et al, 1988). Higher levels of ammonium cannot only be due to uptake from the environment but also result from the catabolism of soluble organic nitrogen in maize roots (Feng et al, 1998). This emphasizes a role of Asn synthetase in ammonium assimilation in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high ammonium in the culture media caused decreased sugar in the terrestrial Phaseolus vulgaris (Mehrer et al 1989) and wheat (Cramer et al 1993) and increased amino acids in the aquatic macrophyte Stratiotes aloides (Smolders et al 1996). It was assumed that ammonium assimilation may result in depletion of soluble sugar (Feng et al 1998) and thus may retard plant growth (Cramer et al 1993). In our study, there was enhanced amino acid synthesis at higher ammonium levels, with 5 mg/L external N&-N possibly being a threshold of assimilation for f!…”
Section: Methodsmentioning
confidence: 99%
“…crispus reminded us to be more prudential before postulating that the depletion of soluble sugar was most the result of ammonium assimilation (Cramer et al 1993). Based on the assumption that glutamine is the main product of ammonium assimilation and that synthesis of 1 mole glutamine costs 0.505 mole glucose (Schubert 1980, Feng et al 1998, in our study the loss of soluble sugar at 20 mg/L N&-N compared with the control should be equivalent approximately to a synthesis of 15 mg glutamine, which is much greater than the maximum free amino acid content of 2 mg found in P: crispus. Therefore, processes other than amino acid synthesis were operating to reduce sugar in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Physiological studies have demonstrated that NH 4 ϩ fluxes commonly exceed those of NO 3 Ϫ from equimolar solutions, and when both ions are present, NO 3 Ϫ influx is reduced within minutes of exposure to NH 4 ϩ (Lee and Drew, 1989;Gazzarini et al, 1999;Kronzucker et al, 1999). As a byproduct of photorespiration and the shikimic acid pathway, as well as through the turnover of various nitrogen pools, large quantities of NH 4 ϩ are also generated internally (Joy, 1988;Feng et al, 1998). Although much of this NH 4 ϩ is re-assimilated through the activity of Gln synthetase (GS), many plants show high values of NH 4 ϩ efflux, and some develop symptoms of toxicity when exposed to millimolar concentrations of NH 4 ϩ in nutrient media, particularly when NH 4 ϩ is the sole source of nitrogen.…”
Section: Ammonium (Nhmentioning
confidence: 99%